2016
DOI: 10.1111/tbed.12552
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Schmallenberg Virus in Belgium after 3 Years of Epidemiological Silence

Abstract: In spring 2016, three years after the last reported outbreak of Schmallenberg virus (SBV) in Belgium, an abortion was notified in a two year old Holstein heifer that previously had not been vaccinated against SBV. The autopsy of the eight-month-old malformed foetus revealed hydrocephalus, torticollis and arthrogryposis. Foetal brain tissue and blood were found to be SBV-positive by RT-PCR and ELISA tests, respectively. Evidencing the circulation of SBV in Belgium in the autumn 2015 is important to anticipate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 5 publications
7
26
0
1
Order By: Relevance
“…Our estimates of EIP support the empirical findings in Denmark and other European countries [ 14 , 17 , 48 ]. On September 30th, the mean EIP of Schmallenberg virus was 21 days using hourly maximum temperatures, 35 days using random resting-site temperatures, 49 days using DMI temperatures and 60 days using hourly minimum temperatures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our estimates of EIP support the empirical findings in Denmark and other European countries [ 14 , 17 , 48 ]. On September 30th, the mean EIP of Schmallenberg virus was 21 days using hourly maximum temperatures, 35 days using random resting-site temperatures, 49 days using DMI temperatures and 60 days using hourly minimum temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Pregnant ewes and cows infected in mid to late November will give birth to malformed lambs/calves around March-April and August-September the following year. Schmallenberg virus has recently been identified in aborted sheep/cattle during spring in Belgium [ 48 ] and in Denmark [ 4 ]. We found a relatively long season of transmission when modeled with microclimatic temperature compared to that of DMI temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In some farms from Li ege and Namur, however, between 50% and 100% of the sampled animals were found SBV antibody-positive at that time. The high within-herd seroprevalence in these provinces seems to be in line with the detection of some aborted SBV RNA-positive calves in those regions in spring 2016 by the Belgian reference laboratory (CODA-CERVA (Veterinary and Agrochemical Research Centre), personal communication; Delooz et al, 2016), further indicating that an SBV recirculation took already place in this region in 2015.…”
Section: Resultssupporting
confidence: 68%
“…Using the microclimatic temperatures of 2015, we found that complete virus development was possible in a period of at least 2.5 months for dengue, 4 months for malaria, 4.5 months for Dirofilaria and West Nile Virus, and 5 months for bluetongue and Schmallenberg virus. In recent years, Schmallenberg virus has been detected in late autumn (September) in Denmark and other European countries 26 . When using meteorological temperature in our transmission model, the Schmallenberg virus did not develop after mid-August in 2015.…”
Section: Discussionmentioning
confidence: 99%